The role of inflammatory cells in fostering pancreatic cancer cell growth and invasion - Evans, Anthony; Costello, Eithne (Frontiers in Physiology, 2012)
The pancreatic ductal adenocarcinoma (PDAC) microenvironment accommodates a variety of cell types and a plethora of complex interactions between tumour cells, host cells and extracellular matrix components. Here we review the role of inflammatory cells, in particular mast cells, myeloid-derived suppressor cells, macrophages, T regulatory cells, T helper cells and neutrophils. The picture that emerges is that of a tumour microenvironment, in which the immune response is actively suppressed, and inflammatory cells contribute in a variety of ways to tumour progression.